In Search of (the Exiled) Identity of the Survivor: About the Protagonist of Jadwiga Maurer’s Stories - Panas, Paweł (Porównania, 2022)
The article is devoted to the problem of the identity of the main character of Jadwiga Maurer’s stories. She is a Jewish girl survivor of the Holocaust who emigrates to Munich, Germany, after the war. Detailed analyses of Maurer’s short stories, arranged in a kind of cycles, reveal that at the identity level, Holocaust rescue was linked to the source experience of exile. The experience of exile after the war became for the main character of Maurer’s prose a kind of cognitive matrix organizing her experience of reality, as well as setting the axiological framework of existential choices.